The effectiveness of choreography in the formation of the coordination skills in first graders - Chuprun, Natalia; Kravchenko, Tetiana; Zakopailo, Serhiii; Bilous, Olesia; Polishchuk, Vitalii; Tsaruk, Viktoriia; Potuzhnij , Oleksandr; Hrdzelidze, Serhii; Kryvenko, Iurii (Eurasian Exercise and Sport Science Association, 2020)
PURPOSE: examine the effectiveness of influence choreography on formation coordination skills of first-graders. METHODS: pedagogical testing: holding posture with open eyes (c); shuttle running 3x10m.,s; running on the spot during 10s, 30s, 60s, (s); walking in the straight line without a visual guide, (sm); throwing rings on a tripod from a distance 1,5m, 2,5m, 3,5m, (number of hits); game task “Transmit telegram”, (one point); three moves forward with the exit (s); carpal dynamometry in full force and 50% from maximal power, (kg). Methods of mathematical statistic. Research was conducted on base of school №7 in Pereiaslav-Khmelnytskyi. In the experiment took part pupils of the first form total quantity 53 individuals (22 girls and 31 boys) of the main medical group of health. RESULTS: it was discovered, that purposeful pedagogical influence of choreography on the informative indexes (girls – skills to: differentiation of muscular efforts, spatial orientation and coordination of moves; boys – skills to management of temporal, power and spatial parameters of moves; a sense of time and a sense of balance), risen effectiveness of formation the main components of first-graders’ coordination skills. CONCLUSIONS: it was installed, that increase of indexes in experimental group higher than in control. In this way, conducting pedagogical experiment confirmed effectiveness of using choreography with purpose of rising formation of the main components of the first-graders’ coordination skills.
Keywords: dance; a sense of equilibrium; a sense of rhythm; coordination of moves